Numerical study of particle fouling deposition on heat transfer surface - Zhiming Xu; Jinhui Li; Zhimin Han (Energy Storage and Saving, 2022)
An integrated Eulerian model for fouling in turbulent flow was developed to simulate the particle fouling characteristics. The model comprises a deposition process and removal process. The deposition process considers four various factors affecting the particle deposition which are Brownian and eddy diffusion, gravity, thermophoretic, and turbophoretic forces. This study compares the Lagrangian and Eulerian approaches under the same operating conditions with an emphasis on their performance in predicting particle deposition. The deposition height calculated by using the Eulerian approach is in good agreement with the experimental data and the deposition morphology is similar to that observed in experiments. Furthermore, this paper explores the deposition characteristics and predicts the deposition morphology under different particle sizes.